QUESTÕES AMBIENTAIS NO ENSINO DE CIÊNCIAS: A EDUCAÇÃO CIENTÍFICA PELO VIÉS DAS ATIVIDADES LÚDICAS. - COELHO, Amanda Marcos (2019)
This research aimed to outline a panorama of conceptions of teachers of the 4th and 5th year of elementary school of the Public Education Network of São Luís - MA, regarding the treatment of environmental issues in the classroom, occasionally on the theme water, with the purpose of understanding the dynamics of teaching practice with scientific knowledge worked in the school field, with the proposition to base a playful resource as a research product, directed as a suggestion for the teaching of that theme the curricular component of sciences of the series mentioned. In this sense, this work was elaborated from the perspective of the qualitative approach, since we entered the school floor and verified the course of implementation of pedagogical activities that embrace precepts of STC and environmental issues. In view of this, the results revealed that teachers have an understanding of the importance of teaching work in relation to environmental issues. Most of them highlighted the theme "Water" as an object in their teaching projects and stated that they work on environmental issues on an annual basis. We noticed inconsistencies in the fact that there are gaps in the way work is done and in the execution of the project on this environmental theme. We were surprised by the fact that the revelations of the teachers' initial conceptions highlighted the importance of scientific language in environmental issues, but it was noticeable that the work of Science is superficial, therefore still needs to be improved mainly in the possibility of providing practical experiences to students, because they evidenced in their speeches the work in a traditional way. In short, it was understood that the objective of analyzing the pedagogical practices of teachers of this pole of schools was achieved, because through such analyses we idealized a pedagogical catalog with games supported by the CTS approach.